Human values: Validation of the Portuguese version of Picture-Based Value Survey for Children - Tendais, I.; Ramos, A.; Alvarez, E.; Rodrigues, R. B. (32nd International Congress of Psychology, 2021)
Research with adults has demonstrated that human values are powerful predictors of a wide range of behaviors. Research with children is still very recent, mainly due to the lack of age-appropriate instruments. The Picture-Based Value Survey for Children (PBVS-C) is a promising new measurement tool that was developed within the conceptual framework of Schwartz’s (1992) theory of human values. The aim of this study was to test the structural validity of the Portuguese version of the PBVS-C. An adapted version of the PBVS-C was administered to a sample of 218 Portuguese children (6 to 10-year-olds) attending two public elementary schools. Multidimensional Scaling analyses revealed structural patterns that closely resemble the ones found in adult and adolescent samples. Consistent with some previous studies with children, some deviations to the theoretical model were also found. Importantly, this work is part of a larger longitudinal study that aims to map the basic human values of children and young adolescents, and their association with other factors related to social inclusion and exclusion in the school context. Our longitudinal study is being implemented alongside a curriculum reform in the Portuguese school system which has explicitly acknowledges the development of human values as a main educational outcome. In this presentation we discuss how the research on children’s values can be instrumental to schools, and more specifically how increased knowledge on the development of children’s values and its influence on other educational, socio-economic and cultural factors may provide crucial information for educators and policymakers.